2004
DOI: 10.1093/annonc/mdh021
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 overexpression is an independent marker of poor prognosis of advanced primary ovarian carcinoma: a multicenter study of the GINECO group

Abstract: HER-2 appeared to influence the outcome of advanced ovarian cancer patients included in a clinical trial with prolonged follow-up, thereby suggesting that HER-2 is a potential target for treatment of this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 26 publications
2
68
2
1
Order By: Relevance
“…In other studies, the percentage of c-erb-B2-positive tumors ranged from 15% to 30%. 12,21,22 It is noteworthy that c-erb-B2 overexpression in our series was observed only in carcinomas: mostly in highgrade carcinomas. Surprisingly, despite this correlation with aggressive morphology, results of the survival study did not indicate statistical significance.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In other studies, the percentage of c-erb-B2-positive tumors ranged from 15% to 30%. 12,21,22 It is noteworthy that c-erb-B2 overexpression in our series was observed only in carcinomas: mostly in highgrade carcinomas. Surprisingly, despite this correlation with aggressive morphology, results of the survival study did not indicate statistical significance.…”
Section: Discussionmentioning
confidence: 51%
“…9 Moreover, p70S6K and eIF4E can be activated by pathways that are independent of mTOR, including the Ras-Raf-MEK-ERK pathway. 10 In previous studies, it was observed that epidermal growth factor receptor (EGFR), c-erb-B2, protein kinase B (AKT), and ERK were expressed frequently in ovarian neoplasms [11][12][13][14] ; however, downstream effectors have not been characterized well in these tumors. We hypothesized that very few factors should exist downstream that could relay the oncogenic signal to the ribosomes or nucleus, regardless of the individual oncogenic alterations upstream.…”
mentioning
confidence: 99%
“…Her2/neu overexpression is associated with a poor prognosis for breast, gastric, and ovarian cancer (4)(5)(6). On the basis of these characteristics, Her2/neu is an attractive therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 (erbB2) expression in ovarian cancer is associated with advanced stage, higher recurrence frequency, shorter survival time, and lower sensitivity to platinum-based chemotherapy (11,12). Trastuzumab and pertuzumab are humanized anti-HER2-targeted antibodies with different modes of action (13,14).…”
Section: Introductionmentioning
confidence: 99%